Ergonomics analysis in a virtual environment. (23rd July 2007) - Backstrand, Gunnar; Hogberg, Dan; De Vin, Leo J.; Case, Keith; , Paul Piamonte
Simulation can support the design of an ergonomic workplace by enabling early assessment of ergonomic conditions in a virtual environment. An important feature is the possibility to study alternative solutions or the effect of improvements from an ergonomics perspective. To be able to conduct an efficient and reliable evaluation in a virtual environment, an objective analysis method is essential. Such an analysis method should be integrated in the simulation software, and support a company's everyday ergonomics work process. In order to gain from existing ergonomics knowledge within a company, the possibility to implement such wisdom in the current simulation software becomes important. This paper presents an implementation work done with the purpose of integrating an established ergonomics work process into a virtual environment. It describes the benefits of an ergonomics work process where simulation and evaluation at early stages of a design process are key factors. The paper will also describe the integration process, i.e., the technical issues as well as the change in work methods.